Physiological and nutritional profile of elite female beach handball players from Brazil - Silva, A. S.; Coeli Seabra Marques, R.; de Azevedo Lago, S.; Guedes Santos, D. A.; Lacerda, L. M.; Silva, D. C.; Soares, Y. M. (The Journal of Sports Medicine and Physical Fitness, 2016)
This study evaluated the anthropometric, physiological and nutritional profiles of elite beach handball athletes. Additionally, the cardiometabolic demands of matches were characterized.Six players (24.7±2 years old, 168±0.08 cm, 63.8±7.1 kg) from Brazilian selection, which ranks first in the world, were characterized in terms of aerobic capacities, speeds, anaerobic capacities, muscle power and dietetic profiles. In an official match, heart rate and lactate production were measured.The athletes exhibited a VO2 max of 44.5±4.7 mL/kg/min, a 20-m speed of 3.214±0.43 seconds, a maximal anaerobic power of 337.3±126.3 watts and a long jump muscle power of 210.1±16.6 cm). The athletes had a mean body fat percentage of 24.9±3.0% and balanced macronutrient intakes. During the match, the lactate concentrations were 13.8 mM and 14.1 mM in the middle and at the end of the first set, respectively, and 11.7 mM and 12.0 mM in the middle and end of the second set, respectively. All players, with the exception of the goalkeeper, maintained a median heart rate of at least 123 bpm and no more than 196 bpm.The athletes exhibited only moderate aerobic capacities and better anaerobic and force capacities and high lactate production during the match.